NiSe2 / VN-C / C difunctional electro-catalytic material and preparation method and application thereof

By growing NiSe2/VN with VN as a core on the carbon/carbon matrix, and combining low-density C/C composite materials to form NiSe2/VN-C/C dual-function electrocatalytic material, the existing solution is to solve the problem The problem of insufficient stability of electrocatalysts in strong alkali environments has achieved efficient electrocatalytic performance.

CN119506955AActive Publication Date: 2025-02-25SHAANXI UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411571491.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-25
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

The existing dual-function electrocatalysts perform well in acidic electrolytes, but are not stable under alkaline conditions and have problems with mismatch in catalytic activity, resulting in poor performance when used in strong alkaline environments.

Method used

Using NiSe2/VN-C/C dual-function electrocatalytic material, a uniformly distributed tetrahedral NiSe2/VN with a core was grown on the carbon/carbon matrix to form a heterostructure, and a low-density C/C composite material was combined as a self-supporting substrate to optimize the electronic structure and improve the electrocatalytic performance.

Benefits of technology

In a strong alkaline environment, electrocatalytic hydrogen evolution, electrolytic oxygen production or full water dissolution electrocatalytic properties are significantly improved, reducing the aggregation and poor conductivity of catalytic active materials, and achieving long-term stable electrocatalytic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506955A_ABST
    Figure CN119506955A_ABST
Patent Text Reader

Abstract

The invention discloses a NiSe2 / VN-C / C bifunctional electro-catalytic material and a preparation method and application thereof, the preparation method comprises the following steps: grinding a vanadium source and a nitrogen source in an agate mortar to uniformly mix the vanadium source and the nitrogen source, transferring the mixed powder into a porcelain boat, paving the porcelain boat in a tubular furnace, and keeping the temperature for 2 hours at 700-900 DEG C in an argon atmosphere to obtain black VN powder; taking a nickel source and selenium powder according to the molar ratio of the nickel source to the selenium source being 1: (1-2), taking VN according to the molar ratio of the nickel source to the vanadium source being 1: (0.8-2), adding the materials into an ethylene glycol solution, and uniformly stirring to obtain a mixed solution; transferring the mixed solution into a polytetrafluoroethylene lining of a high-pressure reaction kettle, putting a pretreated C / C composite material into the high-pressure reaction kettle, ensuring that the C / C composite material is immersed in the solution and is well sealed, finally putting the high-pressure reaction kettle into an electric forced air drying oven, carrying out solvothermal reaction, taking out and washing after the solvothermal reaction is finished, and sealing and airing at room temperature to obtain a NiSe2 / VN-C / C sample; the prepared NiSe2 / VN-C / C bifunctional electro-catalytic material is good in electro-catalytic performance, good in stability, simple in preparation method and controllable in morphology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of functional materials, and relates to electrocatalytic materials, and specifically to a NiSe 2 / VN-C / C bifunctional electrocatalytic material and its preparation method and application. Background Art

[0002] As people's concerns about energy and environmental issues continue to grow, the development of clean and renewable energy has become increasingly urgent. Hydrogen is one of the most promising energy sources due to its significant energy density per unit weight, abundant reserves and clean properties. In the future, hydrogen may reduce or even replace traditional fossil fuels such as crude oil, natural gas and coal. The electrocatalytic hydrogen evolution reaction (HER) is of special significance as a production pathway. The energy barrier and overpotential of HER can be reduced by using efficient and stable electrocatalysts, which will significantly improve the energy conversion efficiency of HER [Gautam, S. Sk, U. Pal, Recent advances in solution assisted synthesis of transition metal chalcogenides for photo-electrocatalytic hydrogen evolution, Phys. Chem. Chem. Phys. 24 (2022) 20638–20673]. Platinum (Pt) is widely regarded as the most effective and durable catalyst for HER in acidic and alkaline environments. However, the scarcity and high cost of Pt-based catalysts have greatly limited their practical applications. Therefore, there is an urgent need to explore cost-effective and efficient noble metal-free electrocatalysts as viable alternatives. In recent years, various transition metal oxides, hydroxides, nitrides, phosphides, sulfides and selenides have been widely studied to find electrocatalysts to replace precious metal-based HER catalysts. Vanadium nitride (VN) is a typical transition metal nitride, which not only has the unique properties of transition metal nitrides, such as metallicity, Pt-like electronic structure, etc., but also has unique physical and chemical properties, such as high melting point and corrosion resistance [E. Yuan, M. Zhou, G. Shi, P. Jian, X. Hou, Ultralow-loading single-atom cobalt on graphitic carbon nitrogen with robust Co-N pairs for aerobic cyclohexane oxidation, Nano Res. 15 (2022) 8791–8803]. It is an interstitial compound in which nitrogen atoms are infiltrated into the parent metal V, corresponding to the contraction of the density of states (DOS) of the d band of the parent metal near the Fermi level. The presence of nitrogen ions gives it unique electronic and bonding characteristics, resulting in unique physical and chemical properties, such as excellent electrochemical activity.The main challenge for hydrogen adsorption on VN is its insufficient electron density [Yang, K. Shen, Y. Liu, Y. Tan, X. Zhao, J. Wu, X. Niu, F. Ran, Novel hybrid nanoparticles of vanadium nitride / porous carbon as an anode material forsymmetrical supercapacitor, Nano Micro Lett 9 (2017) 1–15].

[0003] Transition metal disulfides (TMDs) have attracted much attention due to their low price, abundant reserves, and high electrocatalytic HER efficiency [Dong, T. Zhang, X. Feng, Interface-Assisted Synthesis of 2DMaterials: Trend and Challenges, Chem. Rev. 118 (2018) 6189–6235]. NiSe 2 As a new type of transition metal chalcogenide, it has gained a high reputation in the field of electrocatalysis due to its advantages such as high conductivity, low bandgap, high chemical stability and low cost [Ramakrishnan, S. Jo, N. Pitipuech, J. Sohn, Bifunctionality behavior of phase controlled nickel selenides in alkaline water electrolysis application, Electrochim. Acta 354 (2020), 136742]. The 3d orbital of Se may be involved in bonding with metal atoms because its energy level is close to the 3s and 3p orbitals. This electronic structure causes transition metal selenides to have higher metallic properties, which is conducive to the transport and reaction of electrons. In addition, transition metal selenides have the advantages of simple preparation, good catalytic activity and good stability, making them ideal candidate materials for electrochemical water decomposition.

[0004] Combining two or more heterogeneous materials to achieve complementary advantages and improve structural properties is considered to be an effective method to improve catalytic activity. Existing heterogeneous electrocatalysts still have defects such as limited stability, easy poisoning and deactivation after long-term use, special requirements for pH value, temperature or electrolyte concentration, and limited application range. It is worth noting that HER electrocatalysts perform well in acidic electrolytes, while OER electrocatalysts work better under alkaline conditions. The pH mismatch of OER and HER composite electrocatalysts will inevitably lead to poor water splitting performance. Although HER and OER bifunctional electrocatalysts have been developed to simplify water splitting systems and reduce costs, they usually exhibit excellent HER activity and relatively poor OER catalytic activity, and vice versa. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention aims to provide a NiSe catalyst with good electrocatalytic performance and long-term stability in a strong alkaline environment. 2 / VN-C / C bifunctional electrocatalytic material and its preparation method and application, the preparation method is simple and the product morphology is controllable.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A NiSe 2 The preparation method of the / VN-C / C bifunctional electrocatalytic material comprises the following steps:

[0008] Step 1: Grind the raw materials in an agate mortar at a molar ratio of vanadium source to nitrogen source of 1:(4-7) to make them evenly mixed, transfer the mixed powder to a porcelain boat, lay it flat and place it in a tube furnace, and heat it from room temperature to 700-900°C in an argon atmosphere for 1-4 hours. After the program is completed and cooled to room temperature, the obtained black VN powder is obtained;

[0009] Step 2: Take a nickel source and selenium powder at a molar ratio of 1:(1-2) to the nickel source and selenium powder, take the VN prepared in step 1 at a molar ratio of 1:(0.8-2) to the vanadium source, add the nickel source, selenium powder and VN into an ethylene glycol solution, and stir to obtain a mixed solution;

[0010] Step 3: Transfer the mixed solution to the polytetrafluoroethylene liner of the autoclave, put the pretreated C / C composite material into it, ensure that it is immersed in the solution, seal it well, and finally place the autoclave in an electric blast drying oven, set the temperature parameter to 100-170°C, and keep it warm for 10-16 hours. After the reaction is completed and cooled to room temperature, take it out, wash it, seal it and dry it at room temperature to obtain NiSe 2 / VN-C / C specimen.

[0011] The present invention also has the following technical features:

[0012] Preferably, the vanadium source in step 1 includes any one of vanadium trichloride, vanadium acetylacetonate and vanadium sulfate.

[0013] Preferably, the nitrogen source in step 1 includes any one of urea, dicyandiamide and melamine.

[0014] Preferably, the heating rate of the tubular furnace during the calcination process in step 1 is 2 to 10° C. / min.

[0015] Preferably, the nickel source in step 2 includes any one of nickel dichloride, nickel acetylacetonate and nickel nitrate.

[0016] Preferably, the pretreatment method of the C / C composite material described in step three includes: using ultrapure water and ethanol to alternately perform ultrasonic cleaning on the carbon / carbon matrix, each time for 10 minutes, repeated 3 times, and finally placing it in a culture dish and drying it in an electric blast drying oven at 50°C for 6 hours.

[0017] Preferably, the filling ratio of the polytetrafluoroethylene liner in step three is 50%.

[0018] Preferably, the washing in step three is performed by alternately rinsing with ultrapure water and ethanol for 3 to 5 times.

[0019] The present invention also protects a NiSe prepared by the method as described above. 2 / VN-C / C bifunctional electrocatalytic material and its application as electrocatalyst for hydrogen production, oxygen production or complete water splitting in a strong alkaline environment.

[0020] Compared with the prior art, the present invention has the following technical effects:

[0021] The present invention grows uniformly distributed VN-core regular tetrahedral NiSe on a carbon / carbon matrix through a simple two-step method. 2 / VN, NiSe with many exposed active sites and large specific surface area is obtained 2 / VN-C / C bifunctional electrocatalytic material, using VN with high intrinsic activity but insufficient d-band electron density and NiSe with high metallicity 2 Composite to form a heterogeneous structure, which is beneficial to optimize the electronic structure and promote the transfer of charge, thereby enhancing the electrocatalytic hydrogen evolution reaction; at the same time, the use of low-density C / C composite materials as a self-supporting substrate can effectively reduce the serious aggregation of catalytic active materials, poor conductivity and many inactive base surfaces, promote material transfer, and thus improve performance; the material shows good electrocatalytic performance in hydrogen production by electrolysis of water, oxygen production by electrolysis of water or complete water splitting reaction. At a current density of 100 in alkaline solution, the overpotential required for electrocatalytic hydrogen evolution (HER) is only 238mV;

[0022] The present invention adopts an atmosphere free of ammonia and nitrogen, has a simple process, a controllable process, is green and safe, and has a good product morphology. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 NiSe prepared in Example 1 2 XRD pattern of / VN-C / C;

[0024] Figure 2 NiSe prepared in Example 1 2 SEM images of / VN-C / C;

[0025] Figure 3 NiSe prepared in Example 1 2 LSV curve of electrocatalytic hydrogen evolution of / VN-C / C. DETAILED DESCRIPTION

[0026] The specific contents of the present invention are further explained in detail below in conjunction with embodiments.

[0027] Embodiment 1:

[0028] Step 1: Weigh 174.13 mg of vanadium trichloride (VCl 3 ), weigh 294.28 mg of dicyandiamide, ensure that the molar ratio of V source to nitrogen source is 1:7, place the weighed raw materials in an agate mortar and grind for 30 minutes to mix them evenly, transfer the mixed powder to a porcelain boat and flatten it, use a tube furnace at 900°C, in an argon atmosphere, keep warm for 2 hours, and the heating rate is 10°C / min. After the program is completed and cooled to room temperature, the obtained black VN powder is ground for 10 minutes using an agate mortar and collected;

[0029] Step 2: Ultrapure water and ethanol are used to perform ultrasonic cleaning on the carbon / carbon substrate alternately, each time for 10 minutes, repeated 3 times, and finally placed in a culture dish, and dried in an electric blast drying oven at 50° C. for 6 hours for standby use;

[0030] Weigh 237.69 mg of nickel dichloride hexahydrate (NiCl 2 6H 2 O), weigh 79 mg of selenium powder to ensure that the molar ratio of nickel and Se source is 1:1; add the weighed nickel source and selenium powder and 52 mg of VN obtained in step 1 (to ensure that the molar ratio of Ni source to VN is 5:4) to 25 mL of ethylene glycol solution, and stir magnetically for 4 hours to obtain a mixed solution;

[0031] Step 3: Transfer the mixed solution to a 50 mL polytetrafluoroethylene-lined autoclave, put a piece of treated C / C composite material in it, ensure that it is immersed in the solution, seal it well, and keep the volume filling ratio controlled at 50%. Finally, place the autoclave in an electric blast drying oven, set the temperature parameter to 120 ° C, and keep the temperature for 14 h. After the reaction is completed and cooled to room temperature, take out the C / C, rinse it alternately with ultrapure water and ethanol for 3 times, seal it and dry it at room temperature to obtain NiSe 2 / VN-C / C specimen;

[0032] Figure 1 NiSe prepared in Example 1 2 SEM images of / VN-C / C; Figure 1 It can be seen that a tetrahedral NiSe with prefabricated VN as the core is grown on the carbon / carbon matrix. 2 / VN, which is evenly distributed and has a large specific surface area.

[0033] Figure 2 NiSe prepared in Example 1 2 XRD pattern of / VN-C / C; Figure 2 As shown, the C peak at 26.3° is attributed to the matrix; the peaks at 25.858°, 29.945°, 33.579°, 36.893°, 42.861°, and 50.737° are attributed to NiSe. 2 The peaks at 37.7°, 43.8°, 63.7° and 76.5° are attributed to the (111), (200), (220) and (311) crystal planes of VN (JCPDS Card No. 35-0768).

[0034] In a standard three-electrode system, NiSe 2 / VN-C / C was subjected to electrocatalytic tests, such as Figure 3 To evaluate the catalytic activity of the prepared samples, the -1 Linear sweep voltammetry (LSV) tests showed that the electrocatalytic hydrogen evolution performance required an overpotential of 238 mV at a current density of 100.

[0035] In order to evaluate the electrocatalytic oxygen evolution performance of the prepared samples, the -1Linear sweep voltammetry (LSV) tests showed that electrocatalytic hydrogen evolution required overpotentials of 335, 428, and 545 mV at current densities of 100, 500, and 1000, respectively. Similarly, in order to evaluate the electrocatalytic water splitting performance of the prepared samples, the overpotentials were 5 mV·s -1 Linear sweep voltammetry (LSV) tests were performed, and only a voltage of 1.853 V was required for complete water splitting at a current density of 100.

[0036] Example 2

[0037] Step 1: Weigh 348.3 mg of vanadium acetylacetonate (V(CH 3 COCHCOCH 3 ) 3 , weigh 1135.1 mg of melamine, ensure that the molar ratio of V source to nitrogen source is 1:6, place the weighed raw materials in an agate mortar and grind for 30 minutes to mix them evenly, transfer the mixed powder to a porcelain boat and flatten it, use a tube furnace at 800°C, in an argon atmosphere, keep warm for 2 hours, and the heating rate is 10°C / min. After the program is completed and cooled to room temperature, the obtained black VN powder is ground in an agate mortar for 10 minutes and collected;

[0038] Step 2: Ultrapure water and ethanol are used to perform ultrasonic cleaning on the carbon / carbon substrate alternately, each time for 10 minutes, repeated 3 times, and finally placed in a culture dish, and dried in an electric blast drying oven at 50° C. for 6 hours for standby use;

[0039] Weigh 237.7 mg of nickel dichloride hexahydrate (NiCl 2 6H 2 O), weigh 79 mg of selenium powder to ensure that the molar ratio of nickel to Se source is 1:1; add the weighed nickel source and selenium powder and 65 mg of VN obtained in step 1 (to ensure that the molar ratio of Ni source to VN is 1:1) into 25 mL of ethylene glycol solution, and stir magnetically for 4 h to obtain a mixed solution;

[0040] Step 3: Transfer the mixed solution to a 50 mL polytetrafluoroethylene-lined autoclave, put a piece of treated C / C composite material in it, ensure that it is immersed in the solution, seal it well, and keep the volume filling ratio controlled at 50%. Finally, place the autoclave in an electric blast drying oven, set the temperature parameter to 140 ° C, and keep the temperature for 14 h. After the reaction is completed and cooled to room temperature, take out the C / C, rinse it alternately with ultrapure water and ethanol for 4 times, seal it and dry it at room temperature to obtain NiSe 2 / VN-C / C specimen.

[0041] Embodiment 3:

[0042] Step 1: Weigh 236 mg of vanadium trichloride (VCl 3), weigh 945.9 mg of melamine, the molar ratio of V source to nitrogen source is 1:5, the weighed raw materials are placed in an agate mortar and ground for 30 minutes to make them evenly mixed, the mixed powder is transferred to a porcelain boat and flattened, and a tube furnace is used to heat at 800°C, under an argon atmosphere, for 2 hours, and the heating rate is 10°C / min. After the program is completed and cooled to room temperature, the obtained black VN powder is ground for 10 minutes using an agate mortar and collected;

[0043] Step 2: Ultrapure water and ethanol are used to perform ultrasonic cleaning on the carbon / carbon substrate alternately, each time for 10 minutes, repeated 3 times, and finally placed in a culture dish, and dried in an electric blast drying oven at 50° C. for 6 hours for standby use;

[0044] Weigh 256.9 mg of nickel acetylacetonate (Ni(CH 3 COCHCOCH 3 ) 2 ; Weigh 118.5 mg of selenium powder to ensure that the molar ratio of nickel to Se source is 2:3; add the weighed nickel source and selenium powder and 97.4 mg of VN obtained in step 1 (ensuring that the molar ratio of Ni source to VN is 2:3) into 25 mL of ethylene glycol solution and stir magnetically for 4 h to obtain a mixed solution;

[0045] Step 3: Transfer the mixed solution to a 50 mL polytetrafluoroethylene-lined autoclave, put a piece of treated C / C composite material in to ensure that it is immersed in the solution, seal it well, and keep the volume filling ratio controlled at 50%. Finally, place the autoclave in an electric blast drying oven, set the temperature parameter to 150 ° C, and keep the temperature for 14 h. After the reaction is completed and cooled to room temperature, take out the C / C, rinse it alternately with ultrapure water and ethanol for multiple times, seal it and dry it at room temperature to obtain NiSe 2 / VN-C / C specimen.

[0046] Embodiment 4:

[0047] Step 1, weigh 91 mg of vanadium sulfate, weigh 80.06 mg of urea, the molar ratio of V source to nitrogen source is 1:4, the weighed raw materials are placed in an agate mortar and ground for 30 minutes to mix them evenly, the mixed powder is transferred to a porcelain boat and flattened, and a tube furnace is used at 700°C, in an argon atmosphere, and the temperature is kept for 4 hours at a heating rate of 5°C / min. After the program is completed and cooled to room temperature, the obtained black VN powder is ground for 10 minutes using an agate mortar and collected;

[0048] Step 2: Ultrapure water and ethanol are used to perform ultrasonic cleaning on the carbon / carbon substrate alternately, each time for 10 minutes, repeated 3 times, and finally placed in a culture dish, and dried in an electric blast drying oven at 50° C. for 6 hours for standby use;

[0049] Weigh 217.5 mg of nickel nitrate; weigh 118.5 mg of selenium powder, ensuring that the molar ratio of nickel to Se source is 1:2; add the weighed nickel source and selenium powder and 97.4 mg of VN obtained in step 1 (ensuring that the molar ratio of Ni source to VN is 1:2) into 25 mL of ethylene glycol solution, and stir magnetically for 4 hours to obtain a mixed solution;

[0050] Step 3: Transfer the mixed solution to a 50 mL polytetrafluoroethylene-lined autoclave, put a piece of treated C / C composite material in it, make sure it is immersed in the solution, seal it well, keep the volume filling ratio controlled at 50%, and finally place the autoclave in an electric blast drying oven, set the temperature parameter to 100 ° C, and keep the temperature for 16 h. After the reaction is completed and cooled to room temperature, take out the C / C, rinse it alternately with ultrapure water and ethanol for several times, seal it and dry it at room temperature to obtain NiSe 2 / VN-C / C specimen.

[0051] Embodiment 5:

[0052] Step 1: Weigh 236 mg of vanadium trichloride (VCl 3 ), weigh 945.9 mg of melamine, the molar ratio of V source to nitrogen source is 1:5, the weighed raw materials are placed in an agate mortar and ground for 30 minutes to mix them evenly, the mixed powder is transferred to a porcelain boat and flattened, and a tube furnace is used to heat at 800°C under an argon atmosphere for 1 hour, and the heating rate is 2°C / min. After the program is completed and cooled to room temperature, the obtained black VN powder is ground for 10 minutes using an agate mortar and collected;

[0053] Step 2: Ultrapure water and ethanol are used to perform ultrasonic cleaning on the carbon / carbon substrate alternately, each time for 10 minutes, repeated 3 times, and finally placed in a culture dish, and dried in an electric blast drying oven at 50° C. for 6 hours for standby use;

[0054] Weigh 256.9 mg of nickel acetylacetonate (Ni(CH 3 COCHCOCH 3 ) 2 ; Weigh 118.5 mg of selenium powder to ensure that the molar ratio of nickel to Se source is 2:3; add the weighed nickel source and selenium powder and 97.4 mg of VN obtained in step 1 (ensuring that the molar ratio of Ni source to VN is 2:3) into 25 mL of ethylene glycol solution and stir magnetically for 4 h to obtain a mixed solution;

[0055] Step 3: Transfer the mixed solution to a 50 mL polytetrafluoroethylene-lined autoclave, put a piece of treated C / C composite material in it, ensure that it is immersed in the solution, seal it well, and keep the volume filling ratio controlled at 50%. Finally, place the autoclave in an electric blast drying oven, set the temperature parameter to 170 ° C, and keep the temperature for 10 h. After the reaction is completed and cooled to room temperature, take out the C / C, rinse it alternately with ultrapure water and ethanol for multiple times, seal it and dry it at room temperature to obtain NiSe 2 / VN-C / C specimen.

[0056] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a NiSe2 / VN-C / C bifunctional electrocatalytic material, characterized in that: The following steps are involved: Step 1: Grind the raw materials in an agate mortar at a molar ratio of vanadium source to nitrogen source of 1:(4-7) to make them evenly mixed, transfer the mixed powder to a porcelain boat, lay it flat and place it in a tube furnace, and heat it from room temperature to 700-900°C in an argon atmosphere for 1-4 hours. After the program is completed and cooled to room temperature, the obtained black VN powder is obtained; Step 2: Take a nickel source and selenium powder at a molar ratio of 1:(1-2) to the nickel source and selenium powder, take the VN prepared in step 1 at a molar ratio of 1:(0.8-2) to the vanadium source, add the nickel source, selenium powder and VN into an ethylene glycol solution, and stir to obtain a mixed solution; Step three, transfer the mixed solution to the polytetrafluoroethylene lining of the high-pressure reactor, put in the pretreated C / C composite material, ensure that it is immersed in the solution, and seal it well. Finally, place the autoclave in an electric blast drying oven, set the temperature parameters to 100-170°C, and keep the temperature for 10-16h. After the reaction is completed and cooled to room temperature, take it out, wash it, seal it and dry it at room temperature to obtain the NiSe2 / VN-C / C sample.

2. The method for preparing the NiSe2 / VN-C / C bifunctional electrocatalytic material according to claim 1, characterized in that: The vanadium source described in step 1 includes any one of vanadium trichloride, vanadium acetylacetonate and vanadium sulfate.

3. The method for preparing the NiSe2 / VN-C / C bifunctional electrocatalytic material according to claim 1, characterized in that: The nitrogen source described in step 1 includes any one of urea, dicyandiamide and melamine.

4. The method for preparing the NiSe2 / VN-C / C bifunctional electrocatalytic material according to claim 1, characterized in that: The heating rate of the tubular furnace during the calcination process described in step 1 is 2 to 10° C. / min.

5. The method for preparing the NiSe2 / VN-C / C bifunctional electrocatalytic material according to claim 1, characterized in that: The nickel source described in step 2 includes any one of nickel dichloride, nickel acetylacetonate and nickel nitrate.

6. The method for preparing the NiSe2 / VN-C / C bifunctional electrocatalytic material according to claim 1, characterized in that: The pretreatment method of the C / C composite material described in step three includes: using ultrapure water and ethanol to ultrasonically clean the carbon / carbon matrix alternately, each time for 10 minutes, repeated 3 times, and finally placing it in a culture dish and drying it at 50°C in an electric blast drying oven for 6 hours.

7. The method for preparing the NiSe2 / VN-C / C bifunctional electrocatalytic material according to claim 1, characterized in that: The filling ratio of the polytetrafluoroethylene liner described in step 3 is 50%.

8. The method for preparing the NiSe2 / VN-C / C bifunctional electrocatalytic material according to claim 1, characterized in that: The washing described in step 3 is to rinse with ultrapure water and ethanol alternately for 3 to 5 times.

9. A NiSe2 / VN-C / C bifunctional electrocatalytic material prepared by the method according to any one of claims 1 to 8.

10. Use of the Ni3S2 / VN-C / C bifunctional electrocatalytic material as claimed in claim 9 as an electrocatalyst for producing hydrogen or oxygen by electrolysis of water or for overall water splitting in a strong alkaline environment.

Citation Information

Patent Citations

  • Electrocatalyst for growing CuNi bimetallic composite VN on surface of C / C composite material and preparation method and application thereof

    CN117758294A

  • High-efficiency wide-pH self-supporting Cu3P / VN-C / C electro-catalytic material as well as preparation method and application thereof

    CN117845233A